USULAN PENENTUAN TITIK LOKASI PUSAT DISTRIBUSI VAKSIN COVID-19 DI JAWA BARAT - Fitria Dewi Lestari; Zani Rismayanti; Bagas Wicaksono; Muchammad Fauzi (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2021)
COVID-19 became a pandemic that occurred in many countries around the world including Indonesia. On April 4, 2021, confirmed positive cases in Indonesia were recorded at 1,534,255 cases. West Java occupies the highest position recorded on April 10, 2021 amounting to 256,834 cases until July 3, 2021 positive cases have reached 2,228,938 positive cases of Covid-19 virus. Various ways have been done by the government to reduce the growth rate and spread of the Covid-19 virus, one of which is the provision of vaccines to the community. Distribution of vaccines needs to be done as quickly as possible, so an appropriate distribution strategy is needed. This study aims to determine the location of the Covid-19 vaccine distribution center in West Java. The method used in determining the location point of the vaccine distribution center is the Center of Gravity method. Based on the calculations obtained the coordinate point of the location of the Covid-19 vaccine distribution center in West Java is -6.83041 and 107.73030 with a total distribution cost of Rp31,939,000. The location of the vaccine distribution center provides a greater cost value compared to the cost in the initial condition of Rp 30,091,000. In terms of distance, the location of the latest distribution center resulted in a smaller distance of 3055.3 km compared to the initial condition with a total distance of 3389.8 km. The distance produced by the distribution center is shorter so that it will increase the efficiency of delivery time which will make the distribution process faster